Neuroendocrine regulation of gonadotropin secretion in seasonally breeding birds - Ubuka, Takayoshi; Bentley, George E.; Tsutsui, Kazuyoshi (Frontiers in Neuroscience, 2013)
Seasonally breeding birds detect environmental signals, such as light, temperature, food availability and presence of mates to time reproduction. Hypothalamic neurons integrate external and internal signals, and regulate reproduction by releasing neurohormones to the pituitary gland. The pituitary gland synthesizes and releases gonadotropins which in turn act on the gonads to stimulate gametogenesis and sex steroid secretion. Accordingly, how gonadotropin secretion is controlled by the hypothalamus is key to our understanding of the mechanisms of seasonal reproduction. A hypothalamic neuropeptide, gonadotropin-releasing hormone (GnRH), activates reproduction by stimulating gonadotropin synthesis and release. Another hypothalamic neuropeptide, gonadotropin-inhibitory hormone (GnIH), inhibits gonadotropin synthesis and release directly by acting on the pituitary gland or indirectly by decreasing the activity of GnRH neurons. Therefore, the next step to understand seasonal reproduction is to investigate how the activities of GnRH and GnIH neurons in the hypothalamus and their receptors in the pituitary gland are regulated by external and internal signals. It is possible that locally-produced triiodothyronine resulting from the action of type 2 iodothyronine deiodinase on thyroxine stimulates the release of gonadotropins, perhaps by action on GnRH neurons. The function of GnRH neurons is also regulated by transcription of the GnRH gene. Melatonin, a nocturnal hormone, stimulates the synthesis and release of GnIH and GnIH may therefore regulate a daily rhythm of gonadotropin secretion. GnIH may also temporally suppress gonadotropin secretion when environmental conditions are unfavorable. Environmental and social milieus fluctuate seasonally in the wild. Accordingly, complex interactions of various neuronal and hormonal systems need to be considered if we are to understand the mechanisms underlying seasonal reproduction.